Advanced analyses of computed tomography coronary angiography can help discriminate ischemic lesions. (15th September 2018) - Zhang, Jun-Mei; Shuang, Dongsi; Baskaran, Lohendran; Wu, Weijun; Teo, Soo-Kng; Huang, Weimin; Gobeawan, Like; Allen, John Carson; Tan, Ru San; Su, Xi; Ismail, Nasrul Bin; Wan, Min; et al.
Abstract: Background: Computed tomography coronary angiography (CTCA) image analysis enables plaque characterization and non-invasive fractional flow reserve (FFR) calculation. We analyzed various parameters derived from CTCA images and evaluated their associations with ischemia. Methods: 49 (61 lesions) patients underwent CTCA and invasive FFR. Lesions with diameter stenosis (DS) ≥ 50% were considered obstructive. CTCA image processing incorporating analytical and numerical methods were used to quantify anatomical parameters of lesion length (LL) and minimum lumen area (MLA); plaque characteristic parameters of plaque volume, low attenuation plaque (LAP) volume, dense calcium volume (DCV), normalized plaque volume (NP Vol), plaque burden, eccentricity index and napkin-ring (NR) sign; and hemodynamic parameters of resistance index, stenosis flow reserve (SFR) and FFRB . Ischemia was defined as FFR ≤ 0.8. Results: Plaque burden and plaque volume were inversely related to FFR. Multivariable logistic regression analysis identified the best anatomical, plaque and hemodynamic predictors, respectively, as DS (≥50% vs <50%; OR: 8.0; 95% CI: 1.6–39.4), normalized plaque volume (NP Vol) (≥4.3 vs <4.3; OR: 3.9; 95% CI: 1.1–14.0) and NR Sign (0 vs 1; OR: 13.6; 95% CI: 1.3–146.1), and FFRB (≤0.8 vs >0.8; OR: 44.4; 95% CI: 8.8–224.8). AUC increased from 0.70 with DS as the sole predictor to 0.81 after adding NP Vol and NR Sign; further addition of FFRB increased AUC to 0.93. Conclusion: Normalized plaque volume, napkin-ring derived from plaque analysis, and FFRB from numerical simulations on CTCA images substantially improved discrimination of ischemic lesions, compared to assessment by DS alone. Highlights: Quantification of FFRB with reduced order CFD and novel boundary conditions Quantification of normalized plaque volume and napkin-ring sign semi-automatically FFRB and plaque property are quantified in Asian population. Combination of FFRB and plaque property achieved an incremental diagnostic value